Analysis of the Influence of Leadership Style and Job Satisfaction on Turnover Intention Through Job Stress at Customer Service (Frontline) PT. XXX Logistic Company in Jakarta - Gunawan, Hendra (Business and Entrepreneurial Review, 2024)
Turnover intention is a factor of discomfort experienced by agents in a company. Turnover intention needs to get serious attention to the organization, especially to leadership or manager so can applying force leadership properly and improve job satisfaction to reduce job stress in the company. The purpose of this research was to the effect of leadership style and job satisfaction toward Turnover intention through job stress at customer service (frontline) PT. XXX, Logistic Company in Jakarta. The methodology of this research was testing the hypothesis. The data used were primary data collected from the questionnaire. The samples consisted of 164 customer service (frontline) PT. XXX, which were determined through the purposive sampling method. The data were analyzed through the Structural Equation Model (SEM) of AMOS version 23.0 for Windows. The results of the study showed that there has been a negative effect and significance between leadership style and job satisfaction toward Turnover intention through job stress. The role of job stress is very dominant as a mediator the influence of leadership style and job satisfaction toward Turnover intention. The implication of this research is expected that managers can increase the determinants of job stress itself for example by raising job satisfaction (salary, reward, job promotion) applying force leadership properly, and being able to adjust to all work situations.